AN INVESTIGATION INTO THE ADJECTIVES AND THEIR COLLOCATIONS AS MODIFIERS OF NOUN PHRASES IN FOOTBALL COMMENTARIES IN ENGLISH AND VIETNAMESE - Ph. D Ngũ Thiện Hùng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
- This study is aimed at investigating the linguistic features of the adjectives and their collocations as modifiers of noun phrases in football commentaries in English and Vietnamese newspapers - To help the Vietnamese learners of English enhance their competence in comprehending and using modifiers of noun phrases in English and Vietnamese.